PENGARUH MOTIVASI DAN DISIPLIN TERHADAPPRESTASI KERJA KARYAWAN PADA DIREKTORAT POLITEKNIK LP3I JAKARTA - Nova Nila Krisna Nasution (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2020)
Currently there is no doubt that globalization has demanded a lot of change, improvement and increased in various fields. If connected to the human resources needs to be an increase in the quality of labour and the ability to be able to independently and compete. The aim in this research are: 1) To determine the effect of motivation on employee job performance Directorate Polytechnic LP3I Jakarta. 2) To determine the effect on the performance of employees disciplined In Directorate Polytechnic LP3I Jakarta. 3) To determine the effect of motivation and discipline together on the performance of employees In Directorate Polytechnic LP3I Jakarta.Type of research is a descriptive study using a survey method. The sampling technique used is by using simple random sampling. By using simple random sampling, the samples taken were employees Directorate Polytechnic LP3I Jakarta some 45 people. Proven obtained from the ANOVA test results obtained value of F or F count of 39 442 which is greater than the value of F table for N = 45 at 2.81 or 39 442 2.81 with a significant level of 0.000 for 0.000 0.05, it can be said Motivation (X1) and Discipline (X2) jointly influence on Employee Job Performance (Y). While the value of R Square of 0653 means that Motivation and Discipline has the effect of 65.3% against the Employee Job Performance while the remaining 34.7% influenced by other factors not examined by the authors in this study.